Prevalence of HIV‐associated neurocognitive disorder (HAND) in Turkey and assessment of Addenbrooke's Cognitive Examination Revised (ACE‐R) test as a screening tool. Issue 1 (23rd September 2020) - Korten, V; Ay, U; Harı, E; Tigen Tükenmez, E; Gencer, S; Akça Kalem, S; Demirtaş Tatlıdede, A; Gürvit, İH
Abstract : Objectives: We aimed to assess the Addenbrooke's Cognitive Examination Revised (ACE‐R) and three questions (3Qs, European Aids Clinical Society Guidelines) as potential screening tools for HIV‐associated neurocognitive disorder (HAND). In addition, we tried to determine the prevalence and associated factors for HAND among people living with HIV (PLWH) in Turkey. Methods: Persons living with HIV were enrolled from two teaching hospitals between March 2018 and September 2018. Participants underwent screening tools, a neuropsychological test battery (NTB) and an assessment of activities of daily living. HAND was diagnosed according to Frascati's criteria and applying the Global Deficit Score (GDS) approach. A receiver operating characteristic (ROC) curve analysis was performed to compare the predictive accuracy of ACE‐R to that of the NP test battery. Factors associated with HAND were evaluated using multivariate logistic regression analysis. Results: The study sample included 162 participants (94% male). The HAND prevalence was 45.7% [asymptomatic neurocognitive impairment (ANI), 37.7%; mild neurocognitive disorder (MND), 7.4%; HIV‐associated dementia (HAD), 0.6%] according to the Frascati criteria and 31.5% (ANI, 25.9%; MND, 4.9%; HAD, 0.6%) using the GDS. In the ROC analysis, the ACE‐R showed an area under the curve of 0.68 at a cut‐off score of 89. The sensitivity, specificity and correct classification rate of screening tests for HAND diagnosis were as follows: ACE‐R (62.2%, 67%, 64.8%) and 3Qs (10.8%, 88.6%, 53%). In multivariate analysis, only education level (adjusted odds ratio [aOR] = 0.84, 95% CI: 0.76–0.92, P  ≤ 0.001) was an independent risk factor for HAND. Conclusions: HAND is a common comorbidity in PLWH in Turkey. The sensitivities and specificities of 3Qs and the ACE‐R as screening tools are lower than desired.